Research on Working Capital Management Performance of Wuliangye under the Dual Perspective of "Factor + Channel" - Li, Keting; Zeng, Xiangfeng (International Journal of Global Economics and Management, 2024)
As the most liquid asset of an enterprise, working capital runs through the daily production and operation of the enterprise’s various capital flows, and sufficient working capital is an indispensable condition for the enterprise to carry out production and operation activities. The traditional working capital management performance is to analyse each "factor", only focusing on inventory, accounts receivable and other single items for consideration, but ignoring the overall relevance and coordination of working capital. The enterprise’s working capital is divided into different channels for analysis, can be the enterprise procurement, production and sales as a value chain, for each channel of working capital input and recovery efficiency analysis, so that the working capital management more to meet the value of the enterprise’s pursuit of the goal.